Hubungan Kekuatan Otot Lengan Terhadap Kemampuan Servis Bawah Dalam Permainan Bola Voli Pada Siswa Kelas Xi Di Sma Negeri 3 Kabupaten Seluma - Sucipto, Jhulius Afrial; Apriansyah, Dolly (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
The serve is a stroke used to start a game, but it has evolved into a powerful weapon in an attack that can score points. The overhead serve, which involves striking the ball from above the head, is a technique used to initiate play in volleyball. Proper execution of the serve requires consistent practice in terms of timing, intensity, and frequency. With these factors in place, players are expected to understand how to execute accurate serves that can challenge opponents. Effective training methods tailored to the serve’s motion, combined with balanced and appropriate practice, can significantly improve a player’s performance, especially in underhand serves. This study employs a descriptive method with correlational analysis to explore the relationship between variables. The results indicate a significant correlation between arm muscle strength and underhand serve skills in volleyball among 11th-grade students at SMA Negeri 3 Seluma Regency. These findings suggest that enhanced arm muscle strength contributes positively to the development of underhand serve skills in volleyball